Investigating the Relationships between Adolescents' Levels of Cognitive Absorption and Cyberloafing Activities according to Demographic Characteristics - KARACA, FERİDE (TURKISH GREEN CRESCENT SOC, 2018)
Technology today has become a tool that takes place in countless areas of our lives and has users of all ages. Students, especially during adolescence, have been using technology intensely in recent years. The purpose of this research is to determine according to adolescents' demographic characteristics the states of differentiation between their cognitive absorption levels (a socio-psychological variable) and cyberloafing activities they do during class or while studying. The research has been conducted in this direction with a total of 527 students (241 girls and 286 boys) being educated in 6 state schools in Istanbul during the 2016-2017 school year. This study, which uses the relational screening model, employs the Cognitive Acquisition Scale, Cyberloafing Activities Scale, and a personal information form as data collection tools. The study intends to be able to investigate the effect of multiple independent variables on multiple dependent variables by examining the participants' demographic characteristics through the results of the multivariate analysis of variance (MANOVA). Examining the research results shows a significant difference to exist for the levels of cyberloafing activities with cognitive absorption in accordance with the interaction of the variables of computer/smartphone devices. However, as no significant difference was able to be found in the levels of cognitive absorption and cyberloafing according to the interactions of the variables of gender and grade or daily Internet use and parental restrictions, each variable has been examined separately using the independent group t-test and one-way ANOVA testing. The study is also original in that it aims at detecting adolescent students' levels of cognitive absorption, investigating its effect on cyberloafing, and develops suggestions in line with this for resolving the current in-class problems. The result of the obtained findings will guide researchers, teachers, school administrators, and parents on the topic of what can be done to reduce adolescents' levels of cyberloafing activities and cognitive absorption.
Keywords: Cyberloafing; Cognitive absorption; Adolescents; Internet addiction; Technology addiction; INTERNET